Validation of a method for estimating vitamin A absorption efficiency based on compartmental analysis of post-prandial plasma retinyl ester kinetics - Green, Michael; Ford, Jennifer; Green, Joanne (American Society for Nutrition, 2020)
Because good methods are not available to estimate vitamin A (VA) absorption, we evaluated an approach based on modeling retinyl ester response to an oral VA dose.